2015
DOI: 10.1007/s00345-015-1701-6
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative neutrophil–lymphocyte ratio predicts biochemical recurrence in patients with localized prostate cancer after radical prostatectomy

Abstract: High NLR was significantly related to unfavorable clinicopathological outcomes and worse BCR-free survival. Further studies are needed to clarify the correlation between NLR and PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 27 publications
2
38
1
1
Order By: Relevance
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated NLR is independently associated with worse outcomes in cancers of the breast, 1,2 thyroid, 3 colon, 4 stomach, 5 prostate, 6 lung, 7 adrenal, 8 pancreas 9,10 urogenital tract, 11 esophagus 12 and in glioblastoma, 13 as well as hematologic cancers, including multiple myeloma 14 and diffuse large B-cell lymphoma. 15 According to a recent systematic review and meta-analysis including 100 studies and greater than 40,000 patients, high NLR is associated with adverse overall survival (OS) in many solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…N/L oranı ucuz ve kullanımı kolay bir parametre olması sebebiyle prostat kanserinde bu konularda yararlı olma potansiyeli taşımaktadır. Yüz kırk lokalize prostat kanseri hastasını incelediğimiz bu çalışmamızda N/L oranı ile PSA, patolojik evre, Gleason skoru, lenf nodu tutulumu, tümör hacmi, cerrahi sınır pozitifliği ve (14). Radikal prostatektomi uygulanmış 1688 hastanın incelendiği bir başka çalışmada da yüksek N/L oranı (>2,36) yüksek cerrahi evre (T3-T4), lenf nodu invazyonu ve biyokimyasal rekürrenssiz sağkalımla ilişkili bulunmuştur.…”
Section: Discussionunclassified
“…Minardi et al reported that patients with high NLRs had a greater incidence of BCR [18]. Moreover, Lee and colleagues retrospectively analyzed 1367 patients and found that a high NLR was significantly related to unfavorable clinicopathological outcomes and shorter BCR-free survival [17]. Others reported that high NLR was associated with higher BCR risk.…”
Section: Discussionmentioning
confidence: 99%